We Are What We Say: Accent-Inclusive Socio-Pragmatic Research in Universities - Billy James Chavalala (E-Journal of Humanities, Arts and Social Sciences)
This study investigated accent-inclusive socio-pragmatic practices in South African universities, aiming to understand how linguistic diversity shapes communication and social dynamics in academic settings. The study employed a mixed-methods design to gain a comprehensive understanding of accent inclusivity in universities, integrating both statistical analysis and in-depth qualitative insights. Accents, often tied to socio-economic, regional, or cultural identities, were found to trigger biases and stereotyping, leading to marginalization of speakers with non-standard accents. Using interviews, focus groups, and discourse analysis in several universities, the study revealed that accent bias negatively affected academic participation, social inclusion, and self-confidence. Participants reported that accents influenced perceptions of competence and credibility, reinforcing social exclusion and systemic inequities. The findings highlighted a notable absence of institutional policies promoting accent inclusivity. To address these issues, the study recommended socio-pragmatic interventions, such as training programs to confront linguistic biases, increased awareness campaigns about accent diversity, and the integration of inclusive language policies into institutional frameworks. By fostering a culture that values linguistic diversity, universities could strengthen academic and social discourse. The study contributed significantly to scholarship on linguistic justice by emphasizing accent inclusivity as a critical aspect of diversity and equity initiatives in higher education. It advocated for a holistic approach that connects language, identity, and equity, encouraging institutions to create environments where all individuals can express themselves authentically and thrive academically and socially.